Real people with real experiences: The emergence of classroom L2 study feelings over interacting timescales. (August 2019) - Sampson, Richard J.
Abstract: As one aspect of the lived experiences of the real people in our classrooms, learning is intricately intermeshed with our feelings. Emotions such as foreign language anxiety and enjoyment, as well as the diversity and dynamics of feelings in the classroom have received empirical attention. A recurrent quality mentioned is the "momentary" nature of emotions. However, based on a complexity perspective, the current research instead aimed to investigate the interaction of shorter and longer timescales in the emergence of classroom L2 learners' study feelings. The research involved 47 undergraduates studying in a compulsory EFL course over one semester at a Japanese university. Analysis of introspective journal data revealed that participants' interpretations of emotional experience in the classroom often involved sense-making emergent from the here-and-now as well as individualized life experiences transported into the learning context. These longer timescale processes coloured feelings in the classroom, while felt, social experiences in the classroom also fed back to impact longer timescales of learner psychology – such as understandings of personality, identity, beliefs and motivation. Through this nuanced picture, the article urges those involved in teaching and researching second languages to recognize learners as more rounded individual persons.